2019
DOI: 10.1002/cctc.201901904
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Doped Nickel Phosphide Nanosheets Self‐Assembled Microspheres as a High‐Efficiency Oxygen Evolution Catalyst

Abstract: Recently, much attention has been paid to the low-cost, highefficiency and stable non-precious metal catalysts for oxygen evolution reaction (OER). In this work, vanadium (V)-doped nickel phosphide (Ni 2 P) nanosheets self-assembled microspheres supported on nickel foam (Ni 1 V 1 P NSs/NF) were synthesized as a novel OER catalyst by combined processes of hydrothermal method and low-temperature phosphorization. The synthesized Ni 1 V 1 P NSs/NF material shows excellent catalytic activity due to its interconnect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
3
18
0
Order By: Relevance
“…It has been shown that both Ni 12 P 5 and V-Ni 12 P 5 nanoflakes reveal similar XPS survey spectra but the peak positions have been slightly shifted by 1–1.5 eV for P 2p, Ni 2p, and O 1s to a higher binding energy along with an appearance of a tiny small peak at 522 eV attributed to V 2p in the V-Ni 12 P 5 sample as compared to Ni 12 P 5 , which clearly specified the presence of V dopants inside the Ni 12 P 5 crystal. This observation is quite aligned with the recent findings reported elsewhere. The high-resolution XPS spectra of Ni 2p, P 2p, and V 2p core levels have been widely recorded and are shown in Figure b–d.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been shown that both Ni 12 P 5 and V-Ni 12 P 5 nanoflakes reveal similar XPS survey spectra but the peak positions have been slightly shifted by 1–1.5 eV for P 2p, Ni 2p, and O 1s to a higher binding energy along with an appearance of a tiny small peak at 522 eV attributed to V 2p in the V-Ni 12 P 5 sample as compared to Ni 12 P 5 , which clearly specified the presence of V dopants inside the Ni 12 P 5 crystal. This observation is quite aligned with the recent findings reported elsewhere. The high-resolution XPS spectra of Ni 2p, P 2p, and V 2p core levels have been widely recorded and are shown in Figure b–d.…”
Section: Results and Discussionsupporting
confidence: 91%
“…It is observed that there is a small negative shifting by an average of 0.4 eV for all V peaks for V-Ni 12 P 5 as compared to the reported findings. 47,62,64 Thus, these observations conclude that the effective doping of V into the Ni 12 P 5 crystal effectively reshapes the electron density via transferring electrons from Ni to V on the surface of the electroactive material and thereby significantly modifies the electrical and chemical environments of the Ni active centers for the capacitive performance. To further determine the actual dopant amount in the as-prepared material V-Ni 12 P 5 , inductively coupled plasma mass spectrometry (ICP-MS) measurements were performed.…”
Section: Resultsmentioning
confidence: 80%
“…The 15% W-Ni 12 P 5 catalyst delivered the best TOF value: 0.09 s −1 at an overpotential of 350 mV. This is a better value than some of the recently reported OER catalysts, such as V-Ni 2 P (0.059 mol O 2 s −1 at 300 mV), 18 Cu(OH) 2 @CoNiCH NTs/CF (0.01739 mol O 2 s −1 at 300 mV), 38 (0.0453 mol O 2 s −1 at 350 mV), 39 and HPGC@NiFe (0.0396 mol O 2 s −1 at 300 mV). 40 Motivated by the bifunctionality of 15% W-Ni 12 P 5 , and to explore its prospect as a practical catalyst for overall water splitting, we assembled a two-electrode alkaline electrolyzer cell by spreading the catalyst on carbon cloth, both as the HER and OER catalysts.…”
Section: Resultsmentioning
confidence: 63%
“…Figure b shows the deconvoluted high-resolution XPS spectra of the Ni 2p region of Ni-P (survey spectra in Figure S3). For Ni 2 P-H and Ni 2 P-L, the Ni 2p 3/2 peaks can be deconvoluted into two peaks at ∼853 and 856 eV, corresponding to Ni 0 (Ni–P and Ni–Ni bonds) and Ni 2+ caused by the surface oxidation, respectively. , For Ni-P-a, the peak for Ni 0 is almost invisible. This is often observed for the amorphous nickel phosphides that are prone to be oxidized at the surface .…”
Section: Resultsmentioning
confidence: 99%